Diagnosis of hepatocellular carcinoma in cirrhotic patients: a proof-of-concept study using serum micro-Raman spectroscopy - Taleb, I; Thiéfin, G; Gobinet, C; Untereiner, V; Bernard-Chabert, B; Heurgué, A; Truntzer, C; Hillon, P; Manfait, M; Ducoroy, P; Sockalingum, G D (Analyst (London), 2013)
Hepatocellular carcinoma (HCC) is the third most common cause of cancer death worldwide. The development of novel diagnostic methods is needed to detect tumours at an early stage when patients are eligible for curative treatments. The purpose of this proof-of-concept study was to determine if micro-Raman spectroscopy applied to the sera of cirrhotic patients may be an alternative method for rapidly discriminating patients with and without HCC. Serum samples were collected from 2 groups of patients: cirrhotic patients with HCC (n = 37) and without HCC (n = 34). Two different approaches were used, dried serum drops and freeze-dried serum, and micro-Raman spectra were acquired in the point-mode with a 785 nm laser excitation in the spectral range of 600-1800 cm(-1). Spectra were quality-tested and pre-processed (smoothing, baseline subtraction, vector normalization). Using principal component analysis, the 2 classes, corresponding to cirrhotic patients with and without HCC, could not be differentiated. In contrast, the support vector machine method using the leave-one-out cross validation procedure was able to correctly classify the two groups of patients with an overall rate of accuracy of 84.5% to 90.2% for dried serum drops and 86% to 91.5% for freeze-dried serum. These results are promising and support the concept that serum micro-Raman spectroscopy may become a useful diagnostic tool to detect biomarkers in the field of cancer, as described here for distinguishing between cirrhotic patients with and without HCC.